Mechanical and Tribological Properties of SPS-Sintered Y-TZP: The Effect of Sintering Temperature - Dávid Medveď; Jana Andrejovská; Viktor Puchý (Crystals)
This work systematically investigates the influence of two spark plasma sintering (SPS) temperatures (1400 °C and 1600 °C) on the mechanical and tribological properties of two yttria-stabilized zirconia ceramics: 3 mol.% Y2O3 (3Y-TZP) and 1.5 mol.% Y2O3 (1.5Y-TZP). The ceramics’ microhardness, nanohardness, Young’s modulus, fracture toughness, and tribological performance were evaluated. The results show that 3Y-TZP maintains high hardness (Vickers hardness HV ~1300; nanohardness ~17.1 GPa) and stable fracture toughness (~4.2 MPa·m½), nearly independently of sintering temperature. In contrast, 1.5Y-TZP exhibits a critical trade-off: sintering at 1400 °C yields exceptional fracture toughness (~6.2 MPa·m½), but increasing the temperature to 1600 °C causes a sharp drop to ~4.5 MPa·m½. Tribologically, the highest wear resistance under a 5 N load was observed for the 3Y-TZP sample sintered at 1600 °C. These findings suggest that for low-yttria compositions, higher SPS temperatures can trigger detrimental microstructural changes that degrade toughness. The results provide crucial insights for tailoring SPS parameters and Y-TZP compositions for specific high-performance applications, balancing the competing requirements of hardness and fracture toughness.